Orthogonal Generalized Derivation and Left (Resp. Right) Centralizers on Semiprime Ring - Hanan Khalid Mousa; Salah Mehdi Salih (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The object of this article is present the orthogonally of different two concepts. We proved: Assume  and  are orthog gd and l(rr)c on 2-tortion free semiprime ring  s.t.  is commutative then and  are orthog where  is associated derivation of .
Keywords: Derivation; Generalized Derivation; Left Centralizer; Orthogonal; Semiprime Ring